IMPLEMENTASI KEBIJAKAN KETAHANAN PANGAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN PESISIR SELATAN - hasanatul rahmi; Jumiati Jumiati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
The purpose of this study is to find out the implementation of food security policies to improve welfare through food reserve management programs. The aim is to increase the volume of group food reserves to ensure access and adequate food for its members and increase group capital through productive economic endeavors. This study uses qualitative research with a normative-empirical and phenomenal approach. The informants in this study were determined by purposive sampling with a total of 6 people, namely the Head of Planning, the Head of Food Security, the Mayor of Nagari and the Communitys. The data used are primary data and secondary data, derived from field observations or observations, interviews and documentation studies. This data is tested for validity using source triangulation techniques which are then analyzed with qualitative data analysis techniques. The results showed that the process of implementing food security policy in its implementation still needed some improvements such as in terms of resources involved, characteristics of the ruling institutions and responses from implementers. Supporting factors in the implementation of food security policies are built by the government food storage (granary) which is built by the special allocation fund (DAK) in agriculture and is given a budget in replenishing community food reserves. Whereas the saving factor is the lack of community understanding of how the system in managing community food reserves which causes internal problems in groups such as people who borrow grain / rice in storage (granaries) do not return loans according to the agreement. Efforts made by the Department of Food directly met with members of the group to request that loans be returned in accordance with the agreement that had been made so that the stock of community food reserves could still be available in storage areas (granaries). Keywords :Implementation of food security policies, Public welfare, Food reserve management